IDENTIFIKASI KESULITAN BELAJAR SISWA PADA PEMBELAJARAN TEMATIK KELAS IV SEKOLAH DASAR MUJAHIDIN PONTIANAK - Edo Santoso; Hery Kresnady; Rio Pranata (Universitas Tanjungpura, 2022)
This study aims to describe students' learning difficulties in thematiclearning at the Pontianak Mujahidin Elementary School. This researchuses a qualitative research approach and a descriptive type of research.The subjects in this study were one fourth grade teacher and sixstudents at Mujahidin Elementary School Pontianak and their parents.Data was collected by means of observation, interviews, anddocumentation. The results of this study are as follows: (1) the firsttype of learning difficulty faced by students is learning disability,namely dyscalculia where children have difficulty in counting fluently.The second learning difficulty is the Underachievement which is adecrease in children's achievement based on the results of the learningability test which is indicated by incomplete PH (Daily Assessment)results. The third learning difficulty is Slow Learning which is theinability of students to achieve mastery of the material or low masteryof the material. Where students are slow in understanding the material.(2) there are two factors that influence student learning difficulties,namely internal factors and external factors.